HUBUNGAN ORGANISASI DAN INDIVIDU DALAM PERSPEKTIF KONVENSIONAL DAN ISLAM: PENDEKATAN BARU DALAM STRATEGI RETENSI KARYAWAN - Mutmainnah, Andi; Saputri, Jesika; Rika Ayu Dwi Parmitasati, Rika Ayu Dwi; Syariati, Alim (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The relationship between organizations and individuals is a strategic factor in determining the sustainability and performance of an organization. This study aims to analyze how this relationship affects employee retention, both from a conventional and Islamic economic perspective. This study uses a literature study method by referring to various sources of books, journals, and scientific articles. Conventionally, the relationship between organizations and individuals is built through human relations theory, social exchange theory, and psychological contracts, which emphasize aspects of justice, organizational support, and balance of reciprocal relationships. Meanwhile, in the Islamic perspective, work relationships contain the values ​​of amanah, justice, Islamic brotherhood, and are seen as worship that has moral and spiritual dimensions. The results of the study show that a positive relationship between organizations and individuals, both with a modern humanistic approach and Islamic values, contributes significantly to increasing employee loyalty, job satisfaction, and retention. Organizations that are able to integrate these principles will be more effective in retaining quality workers and ensuring long-term operational sustainability. Keywords: organizational and individual relationships, employee retention, social exchange theory, Islamic economics, Islamic work ethics.